Internal and external silica dust exposure threshold as an early screening index for silicosis: a cross-sectional study - Liu, Shupeng; He, Hailan; Chu, Lei; Song, Qiong; Zhai, Yuesong; Yang, Fang; Liu, Heliang (Frontiers in Public Health, 2025)
IntroductionCommon occupational hazards such as lead, chromium, and mercury have clear biological detection thresholds, but silicon dioxide does not. Therefore, this study aims to determine silica dust exposure thresholds internal and external exposure to identify early screening markers and help screening for susceptible individuals and prevent silicosis.MethodsBasic information, including physical examination data and questionnaires, was collected from the study participants. Blood and urine samples from iron mine workers were also collected as biological specimens. Silicon levels in these samples were measured using ICP-MS, and cumulative dust exposure was calculated based on an on-site hygiene investigation of the mine.ResultsOverall, 1,964 participants were included in the study: 1,823 in the dust exposure group (without illness) and 141 in the silicosis group (with illness). Analysis revealed that the silicosis group had higher cumulative dust exposure, indicating an elevated external exposure index. Internal exposure indicators, such as elevated blood and urine silicon levels, were identified as risk factors for silicosis. Screening thresholds were determined using receiver operating characteristic curves and restricted cubic splines. The results showed that workers had an average dust exposure duration of 8.5 years. The threshold values were 8.02 μg/L for blood silicon with an area under the curve (AUC) of 0.557, 9.51 μg/L for urine silicon with AUC of 0.647, and 3728.50 mg·years for cumulative dust exposure with AUC of 0.658. When validated with external data from silica-exposed workers, blood silicon had the highest accuracy as an early screening indicator for silicosis.ConclusionBlood silicon, urine silicon, and cumulative dust exposure were initially proposed as early screening indicators for silicosis. Validation with external worker data showed that blood silicon had relatively high threshol reliability as a screening marker.